(untitled) (Research, Society and Development, 2022)
The results of a literature review of articles published in the Revista Brasileira de Ensino de Física (RBEF) and in the Caderno Brasileiro de Ensino de Física (CBEF) are presented, whose theme is the teaching of General Relativity in High School. This is a bibliographic research, since the review covered articles published in all editions of the journals, including special ones, since their inception. Of the 3,897 articles, 2,659 from the RBEF and 1,238 from the CBEF, only six articles were found in the RBEF and two articles in the CBEF that contained discussions, elaboration or application of teaching proposals within the scope studied. It was found that, despite the interest and relevance of the subject, there are few articles that address the theme in High School in these two journals, which shows a gap to be filled.